Video game meets literature : language learning with interactive fiction - Pereira, Joe (2018)
The evolution of language teaching approaches and advances in technology have brought with them changes in how and where languages are learned. One way in which language can be practised in a highly empowering and engaging way is through digital game-based learning (DGBL). Interactive Fiction (IF) is a text-based genre of video game which blends literature and puzzle-solving in a simulated world where the player becomes the protagonist of a narrative and controls her actions, seeing the world through her eyes. IF games respond to natural language input in a meaningful way, making them a unique form of non-linear participatory story-telling. Being both a digital game and a form of electronic literature, playing/reading IF can provide an extremely motivating, engaging and creative language learning experience, implementing all four language skills and many cognitive processes – both in and beyond the classroom.